Restraint Stress Impacts on Behavioral Changes and Adrenal and Kidney Tissue Histopathology of Adult Mice - Davy Reyhanditya; Viona Faiqoh Hikmawati; Nia Kurnianingsih; Fatchiyah Fatchiyah (Fakultas Kedokteran Universitas Brawijaya, 2022)
Restraint stress causes changes in the brain parameters. Little research has been done on the impact of restraint stress on other tissues, including adrenal glands and kidneys. This study aimed to determine the effect of restraint stress on eating behaviors, depressive-like, anxiety-like behaviors, weight gain as well as histopathological changes in the kidneys and adrenal glands. Twenty adult BALB/c mice were assigned into control male, stressed male, control female, and stressed female. Restraint stress was applied two hours/day for 14 days. Tail suspension and open field tests were carried out to perform behavior analyses. Adrenal and kidney histological slides were observed under an Olympus CX-31 microscope and visualized using an Olympus E330 camera. The two-way ANOVA test was used for statistical analysis using GraphPad Prism 9.0.0 software. We found that restraint stress defeat appetite and reduces weight gain particularly in stressed female. However, depressive- and anxiety-like behavior were demonstrated in both sexes. Adrenal and kidney tissues of stressed mice demonstrated a higher number of necrotic cells than control. The pyknosis phase was more common than the karyorrhexis and karyolitic phases. Interestingly, male mice were more receptive to stress than female mice. These findings indicate that restraint stress leads to behavioral changes and cellular defects in the adrenal glands and kidneys, particularly in male mice. The sympathetic activation and hypothalamus-pituitary-axis stimulation are assumed as the underlying stress effect of the restraint procedure. The restraint stress method has the potential to be used in future research on stress-responsive target organs.